(3aJGhi Gdfhhis - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s
(3ChdgG (B:s
(3CeG HYO , abO ESJNQJ Gddg GdYXje ai JQJjH GdaJGhi GdJi dTjNi CHj RcQjG JZeOg Gddg HQMeJg djSgd Ydi ef WGYdgG cTa eSGFdgG s
(3BNQgG (B:s
(3CLGH QVi Gddg Yfg gPG eTghQ ai cJH GdObGFb cJHg Yfg hgPG BNQ eG jSQg Gddg ef JQJjHg hLeYg , hGdMeO ddg fLRJ aJGhi GdfhGhi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3Ydi gGeTgG ebGHdGJs
(3cJHJ HYV GdYfGhjjf hGdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
Keywords: (3Gdabg GdTGaYjs